2011
DOI: 10.2967/jnumed.110.086074
|View full text |Cite
|
Sign up to set email alerts
|

Putative Transport Mechanism and Intracellular Fate of Trans-1-Amino-3-18F-Fluorocyclobutanecarboxylic Acid in Human Prostate Cancer

Abstract: Trans-1-amino-3-18 F-fluorocyclobutanecarboxylic acid (anti-18 F-FACBC) is an amino acid PET tracer that has shown promise for visualizing prostate cancer. Therefore, we aimed to clarify the anti-18 F-FACBC transport mechanism in prostate cancer cells. We also studied the fate of anti-18 F-FACBC after it is transported into cells. Methods: For convenience, because of their longer half-lives, 14 C compounds were used instead of 18 F-labeled tracers. Trans-1-amino-3-fluoro-1-14 C-cyclobutanecarboxylic acid ( 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
110
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 123 publications
(112 citation statements)
references
References 22 publications
1
110
1
Order By: Relevance
“…The correlation between the uptake of radiotracers and the gene expression of amino acid transporter in tumor cells has been evaluated in a number of recent nuclear medicine studies. [25,44] have all been recently reported. However, it should be borne in mind that gene expression levels may not directly correlate with protein levels.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The correlation between the uptake of radiotracers and the gene expression of amino acid transporter in tumor cells has been evaluated in a number of recent nuclear medicine studies. [25,44] have all been recently reported. However, it should be borne in mind that gene expression levels may not directly correlate with protein levels.…”
Section: Discussionmentioning
confidence: 95%
“…Overexpression of SNAT was observed in gastric cancer [58], human hepatocellular carcinoma [59], breast cancer [60,61], hilar cholangiocarcinoma [62], C6 glioma [63], prostate cancer [25], HeLa epithelial cervical cancer cells, and 143B osteosarcoma cells [64]; and SNAT expression in stomach and breast cancers is also related to Ki-67 [61] and PCNA (proliferating cell nuclear antigen) expression [58] as indicated by proliferative activity.…”
Section: Trans-1-amino-3-[ 18 F]fluorocyclobutanecarboxylic Acid ([ 1mentioning
confidence: 99%
“…Anti-1-amino-3-[ 18 F]-flurocyclobutane-1-carboxylic acid (18F-fluciclovine) is a non-naturally occurring amino acid first synthesized by Dr. Mark Goodman, and initially developed for the evaluation of cerebral gliomas (8). 18F-fluciclovine transport is primarily mediated by sodium-dependent amino acid transporters, specifically system ASC (ASCT2), with contribution by sodium-independent system L (LAT1) (5). Because these amino acid transporters most involved in 18F-fluciclovine transport mediate influx and efflux of amino acids, washout of radiotracer occurs over time.…”
Section: Introductionmentioning
confidence: 99%
“…Several amino acid transporter systems are over expressed in prostate cancer; specifically large neutral amino acid transporters (system L: LAT1, LAT3, and LAT4) and alanine-serine-cysteine transporters (system ASC: ASCT1 and ASCT2) (5,6). Of these, LAT3, ASCT1, and ASCT2 are upregulated with androgen simulation and LAT1 and ASCT2 are associated with a more aggressive tumor phenotype (7).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, several transporter proteins for amino acids such as leucine and glutamine have been well documented to be upregulated in many types of cancer cells, [3,4] showing their critical role in nutrient signaling to mTOR and cell growth [5]. In addition to amino acid transporter, we have shown that enhanced activity of peptide transport in cancer cells [6,7].…”
Section: Introductionmentioning
confidence: 99%